The sodium iodide symporter (NIS): novel applications for radionuclide imaging and treatment. Issue 10 (3rd September 2021) - Spitzweg, C; Nelson, P J; Wagner, E; Bartenstein, P; Weber, W A; Schwaiger, M; Morris, J C
Abstract : Cloning of the sodium iodide symporter (NIS) 25 years ago has opened an exciting chapter in molecular thyroidology with the characterization of NIS as one of the most powerful theranostic genes and the development of a promising gene therapy strategy based on image-guided selective NIS gene transfer in non-thyroidal tumors followed by application of 131 I or alternative radionuclides, such as 188 Re and 211 At. Over the past two decades, significant progress has been made in the development of the NIS gene therapy concept, from local NIS gene delivery towards promising new applications in disseminated disease, in particular through the use of oncolytic viruses, non-viral polyplexes, and genetically engineered MSCs as highly effective, highly selective and flexible gene delivery vehicles. In addition to allowing the robust therapeutic application of radioiodine in non-thyroid cancer settings, these studies have also been able to take advantage of NIS as a sensitive reporter gene that allows temporal and spatial monitoring of vector biodistribution, replication, and elimination – critically important issues for preclinical development and clinical translation.